2020
DOI: 10.1128/aem.02911-19
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sphingolipid Synthesis Improves Osmotic Tolerance of Saccharomyces cerevisiae

Abstract: To enhance the growth performance of Saccharomyces cerevisiae under osmotic stress, mutant XCG001, which tolerates up to 1.5 M NaCl, was isolated through adaptive laboratory evolution (ALE). Comparisons of the transcriptome data of mutant XCG001 and the wild-type strain identified ELO2 as being associated with osmotic tolerance. In the ELO2 overexpression strain (XCG010), the contents of inositol phosphorylceramide (IPC; t18:0/26:0), mannosylinositol phosphorylceramide [MIPC; t18:0/22:0(2OH)], MIPC (d18:0/22:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…These works highlight that different membrane compositions can be advantageous toward the same stress agent. In both works, Yin et al (2020) and Zhu et al (2020) , the levels of PS and PE were increased, 35.5% and 15, 25.2, and 18.9%, respectively. However, when ELO2 was overexpressed the levels of PC, PA, and PI did not change.…”
Section: Membrane Engineering In Microbial Workhorsesmentioning
confidence: 93%
See 1 more Smart Citation
“…These works highlight that different membrane compositions can be advantageous toward the same stress agent. In both works, Yin et al (2020) and Zhu et al (2020) , the levels of PS and PE were increased, 35.5% and 15, 25.2, and 18.9%, respectively. However, when ELO2 was overexpressed the levels of PC, PA, and PI did not change.…”
Section: Membrane Engineering In Microbial Workhorsesmentioning
confidence: 93%
“…Through an adaptive laboratory evolution experiment, Zhu et al (2020) were able to isolate a strain with improved tolerance to osmotic stress. Transcriptome sequencing (RNA-seq) suggested that mRNA levels of ELO2 were differentially upregulated in the isolated strain.…”
Section: Membrane Engineering In Microbial Workhorsesmentioning
confidence: 99%
“…Plants also contain traces of another four C18 LCBs (d18:2(4E,8E), d18:2 (4E,8Z), t18:2 [with unknown structure], and a unique d18:1 [with a C10=C11 double bond]), one C20 LCB t20:0, and special d21:1 or d22:1 LCBs (the last two LCBs contain a C7=C8 double bond), which have been validated by either mass spectrometry (MS) or nuclear magnetic resonance (NMR) ( Kimberlin et al., 2013 ; Ngo et al., 2020 ; Panzenboeck et al., 2020 ; Wang et al., 2020a ). However, the two common LCBs d20:0 and d20:1, which are detected in animals and Saccharomyces cerevisiae , are rarely reported in plant samples ( De Castro Levatti et al., 2017 ; Zhu et al., 2020 ).…”
Section: Sphingolipid Diversitymentioning
confidence: 99%
“…Moreover, an engineered yeast strain showed a 14.2% increase in the final biomass compared with that of the control (Yin et al, 2020). (3) The membrane functions, including membrane integrity, membrane fluidity, and membrane permeability, can be regulated by engineering the membrane lipid profile (Z. Tan et al, 2017; G. Zhu et al, 2020) and transcriptional factors (Ling et al, 2015). As an example, to increase the stress tolerance caused by octanoic acid, Z. Tan et al (2017) successfully increased octanoic acid stress tolerance in E. coli via the combinatorial deletion of ompF and increased expression of fadL .…”
Section: Introductionmentioning
confidence: 99%